A Review on Enteric Coated Tablet - Singh, Ashwani; Bansal, Dr. Mayank; Gupta, Dr. Rakesh (Journal of Biomedical and Pharmaceutical Research, 2022)
Some of the purpose of tablet coating are masking flavour, fragrance overlapping, Environmental protection, prevent drug from gastric acid .Enteric coated tablets are solid unit dosage forms which are designed to bypass the stomach and release the drug in small intestine and are meant for oral administration. The word “enteric” indicates small intestine; therefore enteric coatings prevent release of medication before it reaches the small intestine.Most enteric coating works by presenting a surface that is stable at the highly acidic pH found in stomach, but breaks down rapidly at a less acidic pH. For e.g. they will not dissolve in the acidic juices of the stomach (pH-3), but will in the alkaline (pH7-9) environment present in the small intestine. Materials used for enteric coatings include CAP, CAT, PVAP and HPMCP, fatty acids, waxes, shellac, plastics and plant fibres.